On top of the city: Rooftops, rights to space, and the fight for St Petersburg’s panoramas - Karas, A (2021)
This is a study of St Petersburg’s rooftops. It explores the experience of being on top of the city and demonstrates that, in Russia’s northern capital, the rooftops have become central to the way the city is perceived, both locally and globally. This thesis explores the relationship between built environment and local identity in St Petersburg. Developing from an interest in the urban exploration practice of roofing, the recreational trespass of the city’s rooftops, and hoping to establish why and how the activity has become so popular in St Petersburg, my analysis explores the different uses of the city’s rooftop (and attic) spaces and relates these to social development, urban planning, civic activism, and the local imaginary in St Petersburg.